(untitled) (Bangladesh Journal of Medical Science, 2023)
Introduction:Cecal volvulus is a rare cause of acute abdomen in adults. It accounts for less than 1% of intestinal obstructions and 25-30% of cases of colonic volvulus. Congenital intestinal malrotation is a complex disorder due to incomplete or faulty rotation and fixation of the gut during the fetal life.Cecal volvulus associated with intestinal malrotation is a very rare presentation. Over 16 cases were reported in the literature. Case report:A 44-year-old man with no medical history, presented to the emergency department with a 2-day history of abdominal pain and bloating. On clinical examination, the abdomen was distended and tympanic to percussion, with diffuse abdominal tenderness. Abdominal X-ray (standing) showed a distended large intestine with an airfluid colonic level. CT scan showed a markedly dilated cecum measuring up to 14 cm, which were located in the left hypochondrium. A “whirl sign” and a superior mesenteric pedicle swirl were also noted. Emergency surgery was performed. Intraoperative exploration revealed a cecal volvulus with a largely distended hypermobile cecum located in the left hypochondrium, with preischemic signs within its wall. All the small gut was right-sided and the large gut left-sided, suggestive of mesenterium commune and intestinal malrotation. A right hemicolectomy withileo-transverse anastomosis was done. The postoperative course was uneventful. The patient is on regular follow up and is doing well. Conclusion:We describe a rare case of surgical management of cecal volvulus associated with intestinal malrotation in a middle-aged patient with no medical history. This case highlights the importance of early diagnosis by physical examination and radiological findings to prevent serious complications. Emergent surgery was the key to this successful management and surgical resection could offer better results with lesser recurrence rate. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 445-448